Preliminary Biochemical study of Aqueous, Ethanolic and Alkaloids Extracts of Xanthium Spinosum L. - S.Abdul-Hassan El-shebany, W. (University of Thi-Qar Journal of Science, 2009)
An aquous hot and cold aquous extracts and ethanolic extracts beside alkaloids fraction for Xanthium Spinosum L. have been prepared.Qualitative tests have been carried out for detection of their general chemical composition, and UV-Visible spectra were also obtained. The antibacterial and antifungal activities of extracts were tested by Agar wells diffusion method. Human blood cells were used to determine cytotoxicity for extracts in concentration 500 mg/ml.. No cytotoxic effects were observed by this concentration.